ALKALI-EXTRACTABLE POLYSACCHARIDES IN MARINE SEDIMENTS: ABUNDANCE, MOLECULAR SIZE DISTRIBUTION, AND MONOSACCHARIDE COMPOSITION - Miyajima T.; Ogawa H.; Koike I. (My University, 2001)
Carbohydrates from coastal sediments were characterized using differential extraction and ultrafiltration techniques. Carbohydrates adsorbed on sediment particles were extracted by various combinations of heating, ultrasonic radiation, and alkali treatment, and the extraction efficiencies of these treatments were compared. Heating (121°C, 60 min) in the presence of alkali (Na2CO3, 20 mM) followed by ultrasonication (20 min on ice) yielded maximal recovery. By repeating this extraction three times, 50% (at maximum) of total carbohydrate in the sediment could be extracted to solution. Carbon-based ratios of carbohydrate to total organic carbon in the extracts and residues were 19 to 28% and 10 to 13%, respectively. The major fraction (68-84%) of extracted carbohydrate was found in macromolecular fractions (>10 kDa). The extracted carbohydrates could be precipitated with 80% (v:v) ethanol with a recovery of 74 to 80%. The monosaccharide composition of the ethanol precipitable polysaccharides was then analyzed by capillary gas chromatography and compared with carbohydrates in the insoluble residue fraction. The molecular composition of residual polysaccharides was somewhat variable, presumably depending on whether the sediment was affected by terrestrially derived organic matter, whereas the composition of the extracted polysaccharides was strikingly similar irrespective of depositional environment. Implications of these data for mobility, reactivity, and origins of sediment organic matter are discussed.